Stability Analysis and Parameter Optimization of Deep Excavation Supporting System in Granular Soils - Manman Dong; Pengjiao Jia (Advances in Civil Engineering)
Deep excavations are prone to result in excessive ground surface settlement displacement of surrounding existing structures, which could cause severe economic damage, even casualties. Hence, the optimization of pile parameters and evaluation of the stability of the excavation are of paramount importance. This paper aims to evaluate the security of deep excavation and optimize the parameters of supported piles in granular soils. An excavation case in granular soils is used to evaluate the stability of deep excavation using displacement least squares method. The stability of case history, Changqingqiao subway station, using pile and inner support system is evaluated by using the least square method. Subsequently, the finite element method is used to optimize the critical parameters of the supported piles, and it needs to be emphasized that the correctness and reasonability of the finite element (FE) models are evaluated according to field measurements. The optimum pile diameter and embedment ratio for single- and double-row retaining pile are 1.0 m and 0.4. The maximum vertical displacement of surrounding soil and horizontal displacement of piles can be calculated by the equations obtained in this research which can provide useful guidance for the designing of deep excavation.